JMJD3 and UTX determine fidelity and lineage specification of human neural progenitor cells - Yongli Shan (Nature Portfolio, 2020)
Neurogenesis is an ordered transition from pluriptotent cells to neural precursor cells (NPCs) to neurons. Here the authors show that loss of the lysine demethylases JMJD3 and UTX leads reduced DNA accessibility at neurogenesis loci in human NPCs, and that the chromatin remodeller BAF can rescue differentiation defects.